Effectiveness of an Interventional Program on Nurses' Practices Concerning Nursing Management for Patients with Stroke - Haider Mohammed Haloob Al-Abedi, Khalida Alwan Mansour, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Stroke is the major cause of adult disability and mortality in the United Kingdom. A stroke can have a deleterious effect on patients, their families, and their caregivers. Objective: This study aimed to determine the effectiveness of the interventional program on nurses' practice concerning nursing management for patients with stroke. Methodology: A quasi-experimental research design was utilized. Data was gathered from Al-Sadder Medical City's neurological wards and emergency department in Al-Najaf Al-Ashraf City. All nurses (n = 60) were divided into two groups; thirty nurses in the study group were exposed to the nursing interventional program; thirty nurses were not exposed to the program. The researcher constructed an educational program and instruments to reach the aims of the present study. The program deals with 9 main domains related to nursing management for patients with stroke Two tools were used to measure the effectiveness of the education program the first tool: was a self-administered questionnaire sheet related to socio-demographic data; the second tool: Observational checklist to evaluate nurses' practice regarding the management of patients with stroke Results: The majority of the nurses in both groups are those with an age range of 25–29 years old, and the high percentages of participants in both groups (53.3%) are females in the study and control groups. Overall evaluation of study group practices regarding the management of patients with stroke at the pre-test was poor with a (0.522) mean score, and the post-test was good with a (1.762) mean score. Conclusion: The current study revealed the effectiveness of the interventional program where nurses' practice improved significantly as compared to before implementing the program. Recommendation: The study recommended generalizing implementation of the designed interventional program for nurses as routine hospital management for patients with stroke.